Efeito gastroprotetor do LASSBio-596 em modelo experimental de gastrite aguda induzida por etanol - Sousa, Johnatan Alisson de Oliveira (2018)
The LASSBio-596 prototype is a molecular hybrid of thalidomide (anti-TNF-α drug), sildenafil (phosphodiesterase 5 inhibitor) and arylsufonamide (phosphodiesterase 4 inhibitor). Their anti-inflammatory effects already have been demonstrated in experimental models of acute inflammation of the lung and chronic allergic inflammation. The present study evaluated the gastroprotective effect of LASSBio-596 in a model of ethanol-induced acute gastritis. Pretreatment with LASSBio-596 (0.1, 1, 10 e 20 mg/kg, v.o.) reduced in a manner dose dependent (p<0,05) the percentage of hemorrhagic lesion areas (0.1 mg/kg: 9,36%, 1 mg/kg: 49,18%, 10 mg/kg: 78,03% e 20 mg/kg: 88,92), when compared to the 50% ethanol group pretreated with DMSO. In microscopic analyzes LASSBio-596 (20 mg/kg) reduced epithelial cell loss and hemorrhage. The prototype restored the antioxidant system by decreasing the levels of malondialdehyde (MDA) and reduced consumption of reduced glutathione (GSH). Pretreatment with LASSBio-596 decreased levels of the cytokines TNF-α and IL-1β, as well as a decrease in myeloperoxidase enzyme activity (MPO) and hemoglobin levels. There was a significant reduction of the gastroprotective effect when was given the inhibitor not selective of the synthesis of nitric oxide (L-NAME, 3 mg/kg i.p.) and selective inhibitor for iNOS (1400w, 10 mg/kg i.p), before pre-treatment with LASSBio-596. The prototype also preserved mucous content adhered to the mucosa and did not alter the gastric secretion and its pH. This way, the results found elucidate the gastroprotective effect of LASSBio-596, with possible mechanisms related to the inhibition of oxidative stress and anti-inflammatory events, besides preserving the protective mucus barrier.